Soil Catena Properties of Daher Al- Jabal in South Syria - Husein, Hussam H. M.; Nammora, Tareq; Zaghtiti, Ibrahim; Al-Khateeb, Anwar; Zenyah, Ehsan (International Journal of Environment, 2017)
Soil catena concept is a sequence of soils extends across relief positions and is developed from similar parent material. This study highlighted on the important aspects and properties of soil catena of Daher El-Jabal in Jabal Al-Arab mountainous area South eastern of Syria, by implementing pedologic study in 2010-2012. Six soil profiles have been studied along pedo-genetic transect in order to highlight the soil catena prevailing properties. The results reveal that the soil has formed from igneous basaltic parent casts, related to Neogen era, where reliefs had the key role in the developing of soil solum. Consequently, Entisols were dominated on eroded summits, Inceptisols on back slops and mountain flanks, Mollisols on depressions. Both water erosion of soil surface and leaching inside soil solum processes were responsible for variation of soil texture, as such soils showed evident of changing in particles size distribution as well as in clay content. Cation exchange capacity (CEC) was less than moderate with domination of Magnesium cation. Soil trace elements were poor to somewhat poor. Soil pH values in general were low; which reflect the pedo-genic character of igneous parent material in which soil drifted from. In some cases, where soil body subjected to continuous leaching of soil bases, in particular calcium cation; soil profiles became totally freed from calcium carbonates. Accordingly soil problems related to downing of soil reaction (pH) are more expected to be increasing by time. This is main reason for some physical diseases, which beginning arise on pomes fruits, particularly bitter pit. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 87-107